Comparative Performance Study of Optimal Interval Type-2 Fuzzy PID Controllers with Practical System - Maity, Ritu Rani De; Mudi, Rajani K; Dey, Chanchal (International Journal of Computer Sciences and Engineering, 2020)
In this paper, the input and output scaling factors of the type-2 fuzzy PID Controller (IT2-FPID) are determined using three different optimization algorithms (Cuckoo search (CS), Particle swarm optimization (PSO), and Bee colony algorithm (BCA)) for a first-order integrating plus dead time (FOIPD) model. A comparative performance study is made for these three optimization algorithms in terms of various transient performance indices. The comparative analysis on the experimental results reveals that BCA based optimal IT2-FPID shows better performance on a simulation model whereas CS based optimal IT2-FPID is found to be superior for practical system over other algorithms.